2019
DOI: 10.1017/s1047951119000179
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of sleep apnea in adult patients with congenital heart disease

Abstract: Background:Although sleep apnea is an important disorder associated with cardiac events, data regarding its prevalence and risk factors in adult patients with congenital heart disease are limited.Methods:In this study, patients underwent a sleep study in the hospital. Indications for admission were classified as heart failure, diagnostic catheterisation, interventional catheterisation, or arrhythmia. The prevalence, characteristics, and risk factors of sleep apnea using a type-3 portable overnight polygraph in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…They identified a proportion of 31% of patients with ACHD at high risk of OSA that diverges from our results, mainly due to the employed screening tool. A likewise wider range of defects was evaluated by Harada and colleagues [ 21 ]. Patients with ACHD who required hospitalization and underwent in-hospital overnight polygraphy were retrospectively analysed.…”
Section: Discussionmentioning
confidence: 99%
“…They identified a proportion of 31% of patients with ACHD at high risk of OSA that diverges from our results, mainly due to the employed screening tool. A likewise wider range of defects was evaluated by Harada and colleagues [ 21 ]. Patients with ACHD who required hospitalization and underwent in-hospital overnight polygraphy were retrospectively analysed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that sleep-disordered breathing (SDB) is often associated with CHD. 238 In patients with obstructive sleep apnea syndrome (OSAS), continuous positive airway pressure has been established. 239 Its clinical relevance remains unknown in terms of prognosis in patients with HF and OSAS.…”
Section: E) Treatment Of Sleep-disordered Breathingmentioning
confidence: 99%
“…Blood pressure should be measured or monitored annually in the clinic or at home (Class I). 398 When secondary hypertension is suspected on medical interview, physical examination, and general laboratory examinations, it is important to investigate specific risk factors in ACHD; sleep apnea syndrome, 238 repaired coarctation of the aorta (CoA) and recurrent hypertension, 399 and use of nonsteroidal antiinflammatory drugs. In patients with cyanotic malformations, it may be worth screening for renal impairment, pheochromocytoma, and paraganglioma.…”
Section: B) Management (Table 21)mentioning
confidence: 99%
See 1 more Smart Citation
“…leep-disordered breathing is one of the common complications in patients with adult congenital heart disease (ACHD). 1,2) It is caused by a reduced forced vital capacity (VC) due to the complexity of underlying cardiac defects, cardiomegaly, previous thoracotomies, obesity, scoliosis, and paralysis of the diaphragm in these patients. 3) Multiple causes are responsible for this complication and thus therapeutic strategies need to be multi-targeted.…”
mentioning
confidence: 99%